Resected stage I anaplastic lymphoma kinase‐positive lung adenocarcinoma has a negative impact on recurrence‐free survival. Issue 8 (10th March 2022) - Fujibayashi, Yusuke; Tane, Shinya; Kitazume, Mai; Kuroda, Sanae; Kimura, Kenji; Kitamura, Yoshitaka; Nishio, Wataru
Abstract: Background: The clinical and prognostic implications of anaplastic lymphoma kinase (ALK) status in resected lung cancers remain unclear. In this study we analyzed the prognostic and predictive significance of ALK‐positive among patients with completely resected lung adenocarcinoma. Methods: We retrospectively reviewed 197 patients with lung adenocarcinoma who underwent complete surgical resection and had been tested for their ALK status. We investigated the impact of an ALK‐positive status on the recurrence‐free survival (RFS) and overall survival (OS) and examined the predictive factors for an ALK‐positive status. Results: ALK positivity was noted in 36 (18%) out of 197 patients, and when limited to stage I patients, in 24 (19%) out of 124. In the pathological‐stage I population, while the OS exhibited no significant difference between ALK‐positive and ALK‐negative patients (5‐year OS rate, 81.2% vs. 89.8%, p  = 0.226), the RFS of ALK‐positive patients was significantly worse than that of ALK‐negative patients (5‐year RFS rate, 55.9% vs. 78.8%, p  = 0.018). A multivariate analysis showed that ALK‐positive status (hazard ratio [HR] 3.431, p  = 0.009) was an independent prognostic factor for the RFS. Regarding the relationship between clinicopathological factors and an ALK‐positive status, a high‐grade histological subtype, including solid and micropapillary subtypes (odds ratio [OR] 5.464, p  < 0.001), and never‐smokers (OR 4.292, p  = 0.018) were associated with ALK‐positive. Conclusion: A high‐grade histological subtype and never‐smokers were associated with ALK positivity, and the RFS of ALK‐positive patients was worse than that of ALK‐negative patients among patients with completely resected stage I lung adenocarcinoma. Abstract : In the pathological‐stage I population, the recurrence‐free survival (RFS) of ALK‐positive patients was significantly worse than that of ALK‐negative patients (5‐year RFS rate, 55.9% vs. 78.8%, p  = 0.018). A multivariate analysis showed that ALK‐positive status (hazard ratio [HR] 3.431, p  = 0.009) was an independent prognostic factor for the RFS. Even in cases in an early disease stage, ALK‐positive tumors should be carefully followed after resection.